Microgravity impairs endocrine signaling and reproductive health of women. A narrative review - Cutigni, Michela; Cucina, Giorgia; Galante, Emanuele; Cerri, Matteo; Bizzarri, Mariano (Frontiers in Physiology, 2025)
During space exploration missions the organism is subjected to several challenges. Most of the studies have been performed on male health in space, leaving the focus on sex differences behind. With the development of new biological technologies, attention is now being paid more to how spaceflight conditions affect human reproductive health. In this review, the focus is on how weightlessness disrupts ovarian function and endocrine signaling by affecting the hypothalamic-pituitary-gonadal axis. Emerging evidence suggests that microgravity can impair estrogen production through the suppression of aromatase expression in granulosa cells. This condition leads to a hypo-estrogenic condition that harms the ovulation and the menstrual cycle. Likely, due to reduced estrogen availability, bone density, and cardiovascular health can consequently be severely involved. New studies focus on how space-related deregulation involving ovarian steroidogenesis look like the picture observed in the Polycystic Ovary Syndrome. These similarities open the perspective to counteract pharmacologically the observed abnormalities. However, our knowledge is severely constrained by the limited data available as well by the lack of proper experimental models of investigation. Indeed, much is required in order to acquire a full understanding of endocrine and functional changes occurring during microgravity exposure, including the joint effect of radiation and weightlessness that deserve to be thoroughly investigated to recognize the respective contribution of each one as well as the eventual synergies.